Low LH level does not indicate poor IVF cycle outcomes with GnRh-a single trigger: a retrospective analysis - Li, Xue-Fei; Wang, Qiao-Feng; He, Qi-Qi; Wang, Xue-Jiao; LV, Xing-Yu; Tang, Xiao-Jun; Zhong, Zhao-Hui; Ding, Yu-Bin; Wan, Qi (BMC pregnancy and childbirth, 2022)
To compare the in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) cycle outcomes between patients with low and normal serum luteinizing hormone (LH) levels on the day after a gonadotropin-releasing hormone agonist (GnRH-a) single trigger. We further investigated the efficacy of human chorionic gonadotropin (hCG) retrigger on IVF cycle outcomes in patients with low LH levels after GnRH-a single trigger. We retrospectively analyzed 957 infertile patients (tubal factor, ovulation disorders, male sperm factor, or unexplained infertility) who were treated with IVF/ICSI at the Chengdu Xinan Gynecology Hospital from July 2017 to December 2020. Patients received sufficient GnRH-a single trigger were divided into two groups based on the serum LH levels on the next day of trigger: normal serum LH levels (≥ 10 mIU/mL) group (control group, n = 906) and low LH levels (< 10 mIU/mL) group (experimental group, n = 51). And the efficacy of hCG retrigger on IVF/ICSI cycle outcomes in 10 patients with low LH levels after GnRH-a single trigger. There were no significant differences in IVF/ICSI cycle outcomes, including egg yield, two pronuclei fertilization rate, excellent embryo rate, or live birth rate of frozen-thawed embryos between patients with low and normal LH levels after GnRH-a trigger. It showed significantly higher risk of ovarian hyperstimulation syndrome in the group of low LH levels [ 0.7%(1/137) vs. 8.5%(4/47), P = 0.016] compared with the group of normal LH levels who received GnRH-a single trigger. The hCG retrigger had no obvious efficacy on cycle outcomes in patients with low LH levels, including oocytes retrieved, fertilization rate, embryo conditions, and live birth rate of frozen-thawed cycles. The IVF/ICSI cycle outcomes of patients with low LH levels on the day after GnRH-a administration were similar to those of patients with normal LH levels. Blood LH test might not be required on the day following the trigger. The hCG retrigger did not have any effect on the cycle outcomes, suggesting that immediate retriggering with hCG was unnecessary.